Nano Online 2016
DOI: 10.1515/nano.11671_2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Natural Convection of a Nanofluid in an Inclined Heated Enclosure Using Two-Phase Lattice Boltzmann Method: Accurate Effects of Thermophoresis and Brownian Forces

Abstract: (http://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited.Laminar natural convection in differentially heated (β = 0°, where β is the inclination angle), inclined (β = 30° and 60°), and bottom-heated (β = 90°) square enclosures filled with a nanofluid is investigated, using a two-phase lattice Boltzmann simulation approach. The effects of the inclination angle on Nu number and convection heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The convective heat transfer process was analyzed through the change of Nusselt number on the hot wall. Rao et al [15] and Mahmoud and Morteza [16] also studied the effects of cavity tilt angle on Nusselt number on hot wall and convective heat transfer coefficient. Yao et al [17] utilized LBM to study the heat transfer process of paraffin in square cavity with obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…The convective heat transfer process was analyzed through the change of Nusselt number on the hot wall. Rao et al [15] and Mahmoud and Morteza [16] also studied the effects of cavity tilt angle on Nusselt number on hot wall and convective heat transfer coefficient. Yao et al [17] utilized LBM to study the heat transfer process of paraffin in square cavity with obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was suggested that uniform cooling was essential especially for concentrated solar cells to avoid hot spots and thermal stresses, while cooling itself was not enough 4,5 . Therefore, both passive 6 and active cooling techniques 7‐11 were considered. In active cooling, power is consumed in pumping the coolant medium for heat dissipation, while in passive cooling, no power is needed and consequently, it is cost‐effective compared to active cooling.…”
Section: Introductionmentioning
confidence: 99%
“…They noted significant modification in heat transfer characteristics and flow behaviour with Grashof number, Brownian motion, thermophoresis, enclosure the inclination and amplitude ratios of temperature and concentration. Ahmed and Eslamian [20] deployed a two-phase lattice Boltzmann computational solver and the Buongiorno nanoscale model to study the laminar natural convection in differentially heated inclined and bottom-heated square enclosure, observing that thermophoresis exerts a major influence on heat transfer augmentation and that heat transfer rate is minimized with bottom heating whereas it is maximized by a unique inclination angle which influences the Rayleigh number. The Tiwari-Das model [21] is an alternative nanoscale formulation to the Buongiorno model.…”
Section: Introductionmentioning
confidence: 99%